Morphological and spectroscopic analysis of cellulose nanocrystals extracted from oil palm empty fruit bunch fiber - Dasan, Y.K. (American Institute of Physics Inc., 2015)
This work evaluates the use of oil palm empty fruit bunch (OPEFB) fiber as a source of cellulose to obtain nanocrystalline cellulose (CNC) by acid hydrolysis reaction. The raw OPEFB fibers were pretreated with aqueous Sodium hydroxide at 80°C followed by bleaching treatment and further hydrolyzed with Sulphuric acid at 45°C with limited range of hydrolysis time and acid concentration. The resulting CNC's were characterized for spectroscopic, crystallographic and morphological properties using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffractometer (XRD), Transmission Electron Microscope (TEM) and Atomic Force Microscopy (AFM). Finding of this study shows that the properties of CNC's are strongly dependent on the hydrolysis time and acid concentration. © 2015 AIP Publishing LLC.